Peculiarities and possibilities of independent newspapers: on the basis of «Khaluk» newspaper examples (Herald of Journalism, 2023)
The article examines the role of the republican socio-political newspaper “Halyk” in the information space of the Syra region, analyzes its regular columns and special pages. Independent, private publications make a great contribution to the development of Kazakh journalism. They urgently raise current socio-economic problems related to the situation in the region and the needs of the population. Not every publication can safely write about positive and negative phenomena taking place in modern society. The newspaper “Halyk” was chosen as the object of this research work, since, in our opinion, it is one of the best among independent publications in the Kyzylorda region.The article examines political, social, ideological and cognitive aspects, thematic features of articles published on the pages of the newspaper, and the public positions of the authors of publications.It should be noted that the editor of the newspaper creates the necessary conditions for creative freedom and expression of the thoughts of the publicist.The main goal of the study is to systematize the ways of formation, development and determine the direction of activity of the Halyk newspaper, identifying its influence on the formation of public opinion at the present stage.In the process of working on the article, methods of systematic description, differentiation, comparison, and data analysis were used.As a result of the study, the journalism of the Halyk newspaper was analyzed, which boldly raises important problems of society and publishes the opinion of the people.Specific examples show how the newspaper managed to achieve such a level that it can influence the authorities in solving the problems of ordinary people.The scientific and practical significance of this study lies in the fact that it provides an analysis of searches, the design of an independent newspaper, the features of using infographics, the capabilities of digital technologies and the dissemination of information, and also determines its place in journalism in the region.The article reveals the role of independent publications in disseminating information and shaping public opinion, showing their influence on the study of regional problems and assistance in solving them.
Keywords: regular columns, special pages, periodicals, genres of journalism